Kajian Gaya Kepemimpinan dan Profil Organisasi Terhadap Pencapaian Target Rencana Strategis RS Katolik di Palembang Periode 2015-2016 - Suandi, Martina Ovinda (UI Scholars Hub, 2018)
Strategic plan is an integral part of the business organization. Leadership styles and variable in organization’s profile have an importantrole to attainment the target ofstrategic plan. Thisstudy was analyzing the relationship of leadership style and organization's profile to attain the target of 2015-2016 Catholic Hospitals’ Strategic Plan in Palembang, using cross sectional design with quantitative approach followed by qualitative approach. The study was conducted in two hospitals with B type and C type. The results showed that the dominant leadership style is supporting with the flexibility. Three variable of organizational profile (organization environ, organizational relation and organizational situation) half was not good. While target attainment of the strategic plan based on a balanced scorecard mostly show in not good results. The results of the bivariate analysis shown a significant association among hospital type and organizational situation towards target attainment of the strategic plan. This is supported by the statements of the informant who is a member of the board of directors of the Catholic Hospital in Palembang. Suggestion for hospital and owner: improvement of human resource management system, monitoring, evaluation and follow-up of the strategic plan and the establishment of a health care network from the first-level health facilities to survive in the era of Universal Health Coverage.